Achieving superior strength-ductility balance via heterogeneous structure and successive TWIP+TRIP effects in medium Mn steel - Wen Peng; Feifan Wang; Yunlong Wang; Jun Chen; Jie Sun; Ning Guo; Jiyuan Liu (Journal of Materials Research and Technology)
In the present work, the medium Mn steel with a strength - ductility product of 49.5 GPa·% was fabricated by a hot rolling, quenching and intercritical annealing process. The excellent mechanical property is attributed to the heterogeneous austenite morphologies, i.e., lath, granular and equiaxed austenite, and the successive TWIP + TRIP effects. The present work especially focus on two aspects: i) the evolution of micro-strain between different morphologies of austenite and ferrite during tensile deformation and its impact on the strain hardening caused by the transformation induced plasticity (TRIP) effect; and ii) the strengthening mechanisms of successive twin induced plasticity (TWIP) and TRIP effects in heterogeneous structures. Under different austenite/ferrite micro-strain interactions, the sequence of TRIP effect is in granular, lath and equiaxed austenite grains. Prior to this, the TWIP effect mainly enhance the strength of austenite, particularly equiaxed grains, which act as a high-strength skeleton structure, postponing the initiation of necking.